Decreased Abundance of Akkermansia muciniphila Leads to the Impairment of Insulin Secretion and Glucose Homeostasis in Lean Type 2 Diabetes. Issue 16 (4th June 2021) - Zhang, Jing; Ni, Yueqiong; Qian, Lingling; Fang, Qichen; Zheng, Tingting; Zhang, Mingliang; Gao, Qiongmei; Zhang, Ying; Ni, Jiacheng; Hou, Xuhong; Bao, Yuqian; Kovatcheva‐Datchary, Petia; et al.
Abstract: Although obesity occurs in most of the patients with type 2 diabetes (T2D), a fraction of patients with T2D are underweight or have normal weight. Several studies have linked the gut microbiome to obesity and T2D, but the role of gut microbiota in lean individuals with T2D having unique clinical characteristics remains unclear. A metagenomic and targeted metabolomic analysis is conducted in 182 lean and abdominally obese individuals with and without newly diagnosed T2D. The abundance of Akkermansia muciniphila ( A. muciniphila ) significantly decreases in lean individuals with T2D than without T2D, but not in the comparison of obese individuals with and without T2D. Its abundance correlates inversely with serum 3 β ‐chenodeoxycholic acid ( β CDCA) levels and positively with insulin secretion and fibroblast growth factor 15/19 (FGF15/19) concentrations. The supplementation with A. muciniphila is sufficient to protect mice against high sucrose‐induced impairment of glucose intolerance by decreasing β CDCA and increasing insulin secretion and FGF15/19. Furthermore, β CDCA inhibits insulin secretion and FGF15/19 expression. These findings suggest that decreased abundance of A. muciniphila is linked to the impairment of insulin secretion and glucose homeostasis in lean T2D, paving the way for new therapeutic options for the prevention or treatment of diabetes. Abstract : Intestinal Akkermansia muciniphila is depleted in lean individuals with type 2 diabetes, who have increased 3 β ‐chenodeoxycholic acid ( β CDCA), reduced insulin secretion and fibroblast growth factor 19 (FGF19) expression. A. muciniphila treatment in mice modulates β CDCA levels, stimulates insulin secretion and FGF19 expression, leading to improved glucose metabolism. The way is paved fornew therapeutic options for diabetes prevention or treatment.